Multiple Trophic Markers Trace Dietary Carbon Sources in Barents Sea Zooplankton During Late Summer - Kohlbach, Doreen; Hop, Haakon; Wold, Anette; Schmidt, Katrin; Smik, Lukas; Belt, Simon T.; Keck Al-Habahbeh, Amalia; Woll, Matthias; Graeve, Martin; Dąbrowska, Anna Maria; Tatarek, Agnieszka; Atkinson, Angus; et al. (Frontiers in Marine Science, 2021)
We investigated diets of 24 Barents Sea zooplankton taxa to understand pelagic food-web processes during late summer, including the importance of sea ice algae-produced (sympagic) carbon. This was achieved by combining insights derived from multiple and complementary trophic marker approaches to construct individual aspects of feeding. Specifically, we determined proportions of algal-produced fatty acids (FAs) to reflect the reliance on diatom- versus dinoflagellate-derived carbon, highly branched isoprenoid (HBI) lipids that distinguish between sympagic and pelagic carbon sources, and sterols to indicate the degree of carnivory. Copepods had the strongest diatom signal based on FAs, while a lack of sea ice algae-associated HBIs (IP25, IPSO25) suggested that they fed on pelagic rather than sympagic diatoms. The amphipod Themisto libellula and the ctenophores Beroё cucumis and Mertensia ovum had a higher contribution of dinoflagellate-produced FAs. There was a high degree of carnivory in this food web, as indicated by the FA carnivory index 18:1(n-9)/18:1(n-7) (mean value < 1 only in the pteropod Clione limacina), the presence of Calanus-associated FAs in most of the taxa, and the absence of algal-produced HBIs in small copepod taxa, such as Oithona similis and Pseudocalanus spp. The coherence between concentrations of HBIs and phytosterols within individuals suggested that phytosterols provide a good additional indication for algal ingestion. Sea ice algae-associated HBIs were detected in six zooplankton species (occurring in krill, amphipods, pteropods and appendicularians), indicating an overall low to moderate contribution of ice-associated carbon from rotten late summer sea ice to pelagic consumption. The unexpected occurrence of ice-derived HBIs in pteropods and appendicularians, however, suggests an importance of sedimenting ice-derived material at least for filter feeders within the water column at this time of year.